2022
DOI: 10.1101/2022.05.19.22275026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serial infection with SARS-CoV-2 Omicron BA.1 and BA.2 following three-dose COVID-19 vaccination

Abstract: SARS-CoV-2 Omicron infections are common among individuals who are vaccinated or have recovered from prior variant infection, but few reports have documented serial Omicron infections. We characterized SARS-CoV-2 humoral responses in a healthy young person who acquired laboratory-confirmed Omicron BA.1.15 ten weeks after a third dose of BNT162b2, and BA.2 thirteen weeks later. Responses were compared to those of 124 COVID-19 naive vaccinees. One month after the second and third vaccine doses, the participant’s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Rather, because of recent prior BA.1 infection among a wide swath of the NYC adult population, it may be that those re-infected with BA.2/BA.2.12.1 after a recent BA.1 infection had a lower mean peak viral load due to greater acquired T-cell mediated immunity from prior BA.1 infection. [35][36][37] This could effectively reduce the magnitude of peak SARS-CoV-2 concentration in wastewater, even for roughly the same number of individuals in the population with active SARS-CoV-2 infection. If this is true, it would suggest that wastewater surveillance may be less useful for surge detection soon after a recent widespread surge like BA.1, and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, because of recent prior BA.1 infection among a wide swath of the NYC adult population, it may be that those re-infected with BA.2/BA.2.12.1 after a recent BA.1 infection had a lower mean peak viral load due to greater acquired T-cell mediated immunity from prior BA.1 infection. [35][36][37] This could effectively reduce the magnitude of peak SARS-CoV-2 concentration in wastewater, even for roughly the same number of individuals in the population with active SARS-CoV-2 infection. If this is true, it would suggest that wastewater surveillance may be less useful for surge detection soon after a recent widespread surge like BA.1, and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have analysed immune responses in PWH following three doses of COVID-19 vaccines, although initial reports on individuals with preserved CD4 + T cell count are optimistic (54). In our study of cART-treated PWH in the older age group, we showed that each COVID-19 vaccine dose, regardless of its type, induces binding IgG Abs for spike and RBD in plasma and spike IgG in saliva at levels similar in PWH and age-matched HIV-negative individuals.…”
Section: Longitudinal Modelling Of Cytokine Responses In T Cellsmentioning
confidence: 99%